ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI ADOPSI FINTECH DI INDONESIA: PENDEKATAN KUANTITATIF BERBASIS MODEL TOE DAN UTAUT) - Meiske Erdinarini Anggita; Kurniawati; Yolanda Masnita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research investigates the key factors affecting individuals' intention to adopt Financial Technology (FinTech) services in Indonesia using a quantitative method grounded in the Technology-Organization-Environment (TOE) framework and the Unified Theory of Acceptance and Use of Technology (UTAUT). Data were gathered from 273 respondents through a structured questionnaire. The results indicate that Social Influence, Performance Expectancy, Facilitating Conditions, Electronic Word of Mouth (e-WOM), System Quality, and Bank Image have positive and significant impacts on the intention to use FinTech services, with System Quality emerging as the strongest predictor, followed by Bank Image and Social Influence. Additionally, Government Support positively moderates the relationship between e-WOM and System Quality with usage intention but does not significantly moderate other relationships. These findings highlight the critical role of system quality, brand reputation, social factors, and government support in promoting FinTech adoption in Indonesia. For future research, it is suggested to incorporate additional variables and utilize a longer research period to gain deeper and more comprehensive insights.